PEMANFAATAN TEKNOLOGI KOMUNIKASI SEBAGAI REFERENSI PEMBELAJARAN MAHASISWA STAIN TEUNGKU DIRUNDENG MEULABOH - Fransisca Tassia (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
During the pandemic, in the learning process of the Evaluation Engineering class students, STAIN Teungku Dirundeng Meulaboh was faced with a lack of book references. They could not access book lending in the library, because learning was transferred using online media. Students overcome the lack of reference to learning resources by using online media as an alternative for learning references. Online media as a source of learning media is very helpful for students. This purpose is to find out how the use of online media can help students find learning references. The findings of this study are that learning Evaluation Techniques in the Tarbiyah Department of STAIN Teungku Dirundeng Meulaboh by using online media can help in completing learning tasks. This media can be an alternative source of reference. So, students remain enthusiastic in completing the assignment given. Therefore, online media is very helpful for students in finding references to learning material. So that students can overcome obstacles in finding the learning material provided.